Tools for Teaching Virtual Teams: A Comparative Resource Review. (December 2017) - Larson, Barbara; Leung, Opal; Mullane, Kenneth
As the ubiquity of virtual work—and particularly virtual project teams—increases in the professional environment, management and other professional programs are increasingly teaching students skills related to virtual work. One of the most common forms of teaching virtual work skills is a virtual team project, in which students collaborate with each other at a distance (and sometimes between multiple institutions) to accomplish a shared task. These projects differ from most management topics in their technology requirements. In this comparative review, we describe the features and trade-offs inherent in some of the asynchronous and synchronous communication technology tools commonly used to run virtual team projects.